Systematic literature review of healthcare services for the elderly: trends, challenges, and application scenarios - Guo, Bo; Shukor, Nur Syufiza Ahmad; Ishak, Irny Suzila (International Journal of Public Health Science (IJPHS), 2023)
In recent years, healthcare for the elderly has received attention from researchers worldwide in the context of global aging. This paper provides a comprehensive overview of healthcare services for older people from 2019 to 2023, using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) methodology to screen published papers in the Web of Science database, and identifies three different application scenarios for healthcare services for older people after analyzing the research objectives of the selected papers. This study examined the common health problems and needs of older adults, and the key parameters used to assess healthcare services for this population. This review also explores how healthcare providers can promote healthy aging and prevent age-related diseases in older patients. This study further evaluates the background and application areas of the papers and explains the methodology of the main ideas proposed in the studies. The review concludes with an analysis of the main trends and challenges that are likely to emerge in healthcare services for older people.